Pravni vidiki razrešnice - Bratina, Borut (Podjetje in delo, 2014)
In the article the authors analyze the procedure how shareholders decide at the general meetings along with discussing about profit and to grant discharge for their work to the board members for the past business year. Instead of clear doctrine of the institute of the discharge, there are many varieties in Slovenian practice, which are not in accordance to the established corporate and court practice. That is the reason why authors emphasise the clear stands in comparative theory and practice with the desire to avoid the cause of the damage to the companies and board members in the future with the "excellent" corporate practice.
Keywords: člani; gospodarske družbe; individualne delovne pogodbe; management; prenehanje; uprava; upravljanje; vodenje